ANALISIS PENGARUH CITRA DESTINASI TERHADAP MINAT BERKUNJUNG WISATAWAN DI DESA WISATA TENJOLAYA - Hasna Zakkiah; Oman Sukirman; Dally Nur Arif (Kepariwisataan: Jurnal Ilmiah, 2025)
AbstractThis study examines the effect of destination image on tourist’s visiting intention to Tenjolaya Tourism Village. Destination image represents tourists’ perceptions of a destination, encompassing cognitive, affective, and unique dimensions. In this study, destination image is measured through three indicators: cognitive image, affective image, and unique image, while visiting intention is assessed through transactional, preferential, referential, and exploratory intentions. A quantitative associative approach was employed, with data collected through questionnaires distributed to 383 tourists who had visited Tenjolaya Tourism Village. Data analysis was conducted using rank-based regression and Spearman Rank correlation. The results reveal a correlation coefficient of 0.636 with a significance value of 0.000, indicating a strong and statistically significant relationship between destination image and visiting intention. Furthermore, the coefficient of determination (R²) shows that destination image explains 40.5% of the variation in tourists’ visiting intention. Affective aspects, such as village atmosphere and social interaction, contribute most significantly to increasing tourist’s interest, whereas cognitive aspects, particularly accessibility, still require improvement. These findings suggest that strengthening destination image, especially its emotional and experiential components, is essential for enhancing tourists’ intention to visit and recommend Tenjolaya Tourism Village.Keywords: Destination Image; Tourism Village; Tourist; Visiting IntentionAbstrakPenelitian ini bertujuan untuk menganalisis pengaruh citra destinasi terhadap minat berkunjung wisatawan di Desa Wisata Tenjolaya. Citra destinasi dipahami sebagai persepsi wisatawan yang mencakup aspek kognitif, afektif, dan keunikan destinasi. Penelitian ini menggunakan pendekatan kuantitatif asosiatif dengan melibatkan 383 wisatawan sebagai responden yang dipilih melalui teknik purposive sampling. Data dikumpulkan menggunakan kuesioner skala Likert dan dianalisis dengan regresi rank-based serta korelasi Spearman Rank. Hasil analisis menunjukkan nilai koefisien korelasi sebesar 0,636 dengan tingkat signifikansi 0,000, yang menandakan adanya hubungan yang kuat dan signifikan antara citra destinasi dan minat berkunjung wisatawan. Nilai koefisien determinasi (R²) sebesar 0,405 menunjukkan bahwa citra destinasi mampu menjelaskan 40,5% variasi minat berkunjung. Aspek afektif, seperti suasana desa dan interaksi sosial, memberikan kontribusi terbesar terhadap peningkatan minat wisatawan, sementara aspek kognitif, khususnya aksesibilitas, masih perlu ditingkatkan. Temuan ini menegaskan bahwa penguatan citra destinasi secara menyeluruh berperan penting dalam meningkatkan minat berkunjung wisatawan ke desa wisata.Kata Kunci : Citra Destinasi; Desa Wisata; Minat Berkunjung; Wisatawan